Organizational Commitment as A Mediator of Employee Engagement and Retention Among Non-Teaching Staff: Evidence from Selected Universities in Cebu City - Rico, Madelline E.; Polinar, Mark Anthony N.; Delantar, Alexander Franco A.; Delantar, Jinky R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Employee retention is a critical concern in universities, as frequent turnover is disruptive and increases operational costs. In Cebu City, non-teaching staff play a vital role in sustaining academic services, yet their retention often depends on how engaged and committed they feel toward their institutions. This study examined whether organizational commitment mediates the relationship between employee engagement and employee retention among non-teaching personnel in selected Cebu universities. Using a quantitative correlational design, survey data were gathered from 100 staff members and analyzed through descriptive statistics, Spearman’s rho, and structural equation modeling. Results revealed high engagement, strong organizational commitment, and generally positive retention intentions. Mediation analysis confirmed that while engagement directly predicts retention, commitment strengthens this link by fostering loyalty and value alignment. These findings suggest that recognition, fair policies, and growth opportunities enhance both engagement and commitment, leading to a more stable workforce. The study highlights the importance of non-teaching staff in ensuring institutional continuity and offers insights for higher education administrators on reducing turnover risk.